Front crawl kinematic: Breathing and pace acute effects - Castro, F.; Guimaraes, A. C. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study was to verify the effects of breathing and no breathing and pace on stroke length (SL) and rate (SR) and swimming velocity (SV). Ten Sprinter males performed 6 front crawl trials of 25 m (rest interval: IminSOs). SL, SR and SV were measured under two breathing conditions: breathing to the preferred side every cycle (B) and no breathing (NB), and three paces representatives of: warm up pace, 1500 m freestyle race pace, and 50 m freestyle race pace. Each trial was fllmed with a motion analysis System (60 Hz) from sagital view. A reflective marker was fixed to the swimmer's right wrist to quantify SL and SR. SV was obtained by the SL and SR prod-uct. Under NB conditions, SR and SV increased independent of the pace. The increase of pace was related to decrease of SL and increase of SR and of SV, whatever the breathing condition.